Excess risk of kidney disease in a population living near industrial plants - Hodgson,S; Nieuwenhuijsen,MJ; Hansell,A; Shepperd,S; Flute,T; Staples,B; Elliott,P; Jarup,L (Occupational and Environmental Medicine, 2004)
Runcorn has been a site of chemical industry activity for over a century, where tons of toxic chemicals are released annually to air and water. Excess kidney disease mortality (nephritis, nephrotic syndrome, and nephrosis) was found in the population living within 2 km of the industrial plants (standardised mortality ratio (SMR) in males 131 (95% CI 90 to 185) and females 161 (95% CI 118 to 214)) compared to a reference population (northwest England)). Risk of hospital admissions for kidney disease in Halton (comprising the towns of Runcorn and Widnes) was higher than in the less industrial, nearby town of Warrington. The standardised admission ratio (SAR) in Halton was 115 (95% CI 107 to 124) for males and 126 (95% CI 117 to 137) for females; and in Warrington 91 (95% CI 85 to 97) for males and 84 (95% CI 78 to 91) for females compared to the Warrington and Halton area as a whole. The excess risk of kidney disease in the Runcorn area requires further investigation.